Experimental and numerical study and comparison of performance for wavy fin and a plain fin with radiantly arranged winglets around each tube in fin-and-tube heat exchangers. (25th March 2018) - Li, M.J.; Zhang, H.; Zhang, J.; Mu, Y.T.; Tian, E.; Dan, D.; Zhang, X.D.; Tao, W.Q.
Highlights: The 5-row tubes of LVGs enhanced fin can substitute the 6 rows wavy fin. The 12-LVG fin has the highes Nu number and friction factor compared with other fins. Entransy analysis proves that the proposed fin have better heat transfer performance. Abstract: A new kind of plain plate fin with twelve vortex generators of delta winglets around each tube in fin-and-tube heat exchanger proposed by the present authors is experimentally studied in this paper. Experiments of four heat exchanger surfaces of real size are conducted to compare the comprehensive characteristics of the proposed fin with a circular wavy fin: two wavy fin-and-tube heat exchangers with 6 rows of tubes at the fin pitch of 2.54 mm and 2.117 mm (10-wavy and 12-wavy for short) respectively; and two proposed fin-and-tube heat exchanger surfaces with five rows of tubes at the same fin pitches (10-LVG and 12-LVG) correspondingly. The inlet velocity of the air side varies from 1.5 m/s to 7.5 m/s, and the water side flow rate is fixed at a certain value at each air inlet velocity. Experimental results indicate that the heat transfer rate and pressure penalty of heat exchanger surfaces using proposed fin with five-row tubes are almost the same with the six-row tubes wavy heat exchanger surfaces. Correlation of the Nusselt number Nu and the friction factor f on the air side are achieved. Entransy analysis is conducted to reveal the heat enhancement mechanism.